Research on the Mechanism of Digital Inclusive Finance to Promote Rural Industrial Integration - Jiang, Kai; Zhang, Ping (International Journal of Global Economics and Management, 2024)
The development of digital inclusive finance is of great significance in easing financial exclusion in China’s rural areas and promoting rural revitalization, while an important means of rural revitalization is rural industrial integration. Studying the relationship between digital inclusive finance and rural industrial integration is of great significance in accelerating the construction of agricultural and rural modernization. This paper utilizes the panel data of 30 provinces in China from 2012 to 2022,adopts the entropy value method to calculate the degree of rural industrial integration, and establishes the two-way fixed effect model, the moderating effect model, and the panel threshold model to explore the impact of digital inclusive finance on rural industrial integration and the mechanism of the role of the digital financial inclusion, and the results show that:(1)digital inclusive finance promotes the development of rural industrial integration.(2)The improvement of rural transaction efficiency, the degree of traditional financial competition and agricultural labor productivity enhances the promotion of digital inclusive finance on rural industrial integration. Then corresponding policy advice is given based on the conclusions.